Rab GTPases regulate endothelial cell protein C receptor-mediated endocytosis and trafficking of factor VIIa. - Ramesh C Nayak; Shiva Keshava; Charles T Esmon; Usha R Pendurthi; L Vijaya Mohan Rao (PLoS ONE, 2013)
Recent studies have established that factor VIIa (FVIIa) binds to the endothelial cell protein C receptor (EPCR). FVIIa binding to EPCR may promote the endocytosis of this receptor/ligand complex. Rab GTPases are known to play a crucial role in the endocytic and exocytic pathways of receptors or receptor/ligand complexes. The present study was undertaken to investigate the role of Rab GTPases in the intracellular trafficking of EPCR and FVIIa. CHO-EPCR cells and human umbilical vein endothelial cells (HUVEC) were transduced with recombinant adenoviral vectors to express wild-type, constitutively active, or dominant negative mutant of various Rab GTPases. Cells were exposed to FVIIa conjugated with AF488 fluorescent probe (AF488-FVIIa), and intracellular trafficking of FVIIa, EPCR, and Rab proteins was evaluated by immunofluorescence confocal microscopy. In cells expressing wild-type or constitutively active Rab4A, internalized AF488-FVIIa accumulated in early/sorting endosomes and its entry into the recycling endosomal compartment (REC) was inhibited. Expression of constitutively active Rab5A induced large endosomal structures beneath the plasma membrane where EPCR and FVIIa accumulated. Dominant negative Rab5A inhibited the endocytosis of EPCR-FVIIa. Expression of constitutively active Rab11 resulted in retention of accumulated AF488-FVIIa in the REC, whereas expression of a dominant negative form of Rab11 led to accumulation of internalized FVIIa in the cytoplasm and prevented entry of internalized FVIIa into the REC. Expression of dominant negative Rab11 also inhibited the transport of FVIIa across the endothelium. Overall our data show that Rab GTPases regulate the internalization and intracellular trafficking of EPCR-FVIIa.